К вопросу об особенностях соотношения глиальных элементов в некоторых стволовых формациях головного мозга кролика. Сообщение II - Гончаренко, Л.Е.; Жданова, М.В.; Квитницкая-Рыжова, Т.Ю. (Вестник зоологии, 1973)
The number of astrocytes, oligodendrogliocytes and macrogliocytes of the brain n. caudatus, thalamus opticus, hypothalamus, corpora quadrigemina is calculated in six rabbits. It is established that oligodendrogliocytes dominate in n. caudatus, thalamus op¬ticus, hypothalamus, astrocytes dominate in corpora quadrigemina. Astrocyte and oligodendrogliocyte quantity in hypothalamus is greater than in the other studied brain areas. Microgliocyte quantity in all the studied areas of the brain was constantly the least.